Wood pole overhead lines - Wareing, B. (Brian) (Institution of Engineering and Technology, 2005)
The book reviews developments in the following fields: overhead line design; statutory requirements; surveying and profiling; traditional design standard; probabilistic design standard; mechanical design of pole; mechanical design of cross-arm and foundation; weather loads; conductor sag; tension; conductor characteristics and selection; bare conductor; insulated conductor; covered conductor; line construction; inspection techniques; condition assessment; health indices; overhead line failure mode; wood pole decay mechanism; remedial treatment; line and component susceptibility to weather effects; live line working; and lightning protection.